2021
DOI: 10.1017/inp.2021.20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ventenata dubia removal on rangelands of northeast Wyoming

Abstract: Ventenata dubia (Leers) Coss is one of several annual grass invaders of the western US. Ventenata dubia is documented reducing the forage availability for livestock and wildlife as well as lowering biodiversity in the Great Basin. This species has recently spread to the Great Plains, where it could bring these impacts with it. We attempt to answer questions on whether or not conservation practices, in this case removal of V. dubia with herbicide, results in recovery of forage resources and biodiversity. We ans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…Consistent with this explanation, perennial grass cover at 33 MAT at Site 1 showed a positive response at intermediate and high indaziflam rates (Figure 1C), where B. tectorum density and cover were also lowest at this time (Figure 1A and B). These data support previous studies demonstrating that the positive perennial grass cover responses we observed probably resulted from reduced B. tectorum competition (Clark et al 2020;Hart and Mealor 2021;Sebastian et al 2017a).…”
Section: Perennial Grass Coversupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with this explanation, perennial grass cover at 33 MAT at Site 1 showed a positive response at intermediate and high indaziflam rates (Figure 1C), where B. tectorum density and cover were also lowest at this time (Figure 1A and B). These data support previous studies demonstrating that the positive perennial grass cover responses we observed probably resulted from reduced B. tectorum competition (Clark et al 2020;Hart and Mealor 2021;Sebastian et al 2017a).…”
Section: Perennial Grass Coversupporting
confidence: 93%
“…We expected indaziflam treatments to have no observable impact on the cover of co-occurring perennial grasses based on previous research (Clark et al 2020;Hart and Mealor 2021;Sebastian et al 2016Sebastian et al , 2017a. Consistent with our expectation, we did not observe any negative effects on perennial grass cover (Figures 1C and 2C).…”
Section: Perennial Grass Coversupporting
confidence: 90%
See 3 more Smart Citations